Validity and Reliability of the Indonesian Version of Kidney Disease Quality of Life (KDQOL-36) Questionnaire in Hemodialysis Patients at Hasan Sadikin Hospital, Bandung, Indonesia - Rudi Supriyadi; Fauliza Rakhima; Rubin Surachno Gondodiputro; Guntur Darmawan (Acta Medica Indonesiana)
Background: the prevalence of chronic kidney disease (CKD) and dialysis patients is increasing every year in Indonesia. The impact of CKD and dialysis on patient quality of life (QOL) has been recognized as an important outcome measure in the management of CKD. The Kidney Disease Quality of Life (KDQOL-36) has been validated and is widely used as a measure of QOL for CKD and dialysis patients in many countries, but not in Indonesia. The aim of this study is to determine the reliabity and validity of the Indonesian version of KDQOL-36 on hemodialysis patients in Indonesia. Methods: the KDQOL-36 was translated into Indonesian language by a certified translator and then it was back-translated into English. The translated questionnaire was further reviewed by an expert panel. The final questionnaire was administered to hemodialysis patients in Hemodialysis Unit at Hasan Sadikin General Hospital. Validity was measured using Pearson’s correlation between the kidney disease-targeted scores, generic dimensions (SF-12) scores and each scale score in KDQOL-36. The internal consistensy was assessed using Cronbach’s Alpha and reliability was examined using test-retest. Results: out of 103 patients, we found that most subjects were male (52.4%) with median age of 51 (22-75) years. The duration of hemodialysis was 3.4 (SD 2.1) years. The validity test showed a significant correlation (p<0.001) on kidney disease-targeted total score, SF-12 and each score of the scale within it. All of the KDQOL-36 scales showed good test-retest reliability. Internal consistency reliability values were acceptable, with Cronbach’s Alpha >0,7 for all scales. Conclusion: the Indonesian version of the KDQOL-36 questionnaire is valid and reliable for evaluating QOL in reguler hemodialysis patients.